Various roles of the reticaloendothelial system - Harjani, Harjani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
The reticuloendothelial system is the bodys defence units, which are situated in every tissues layer and tissues folds of the body, and function as one functional unit.Its cellular components have the capacity to move to approach foreign particles by the help of the circulation function or by active amoeboid movements within the tissue, to phagocytose those foreign particles. Some of these cellular components have the capacity to make humoral antibody. Its most important function is to maintain the uniqueness of self, which includes among others:-destruction of foreign particles,-destruction of senile cells of the body, andcancer surveillance.Key Words: emperipolesis, bacterial infection - immediate and delayed hypersensitivity- SlowÂ Reacting Substance of Anaphylaxis - blocking antibody